THE MEDIATING ROLE OF ORGANIZATIONAL CULTURE ON THE RELATIONSHIP BETWEEN LEADERSHIP AND SOCIAL CAPITAL IN THE IRAQI SERVICE SECTOR - Majid, Majid Hamid Hazim; Mohammed, Raghad Raaed (International Journal of Engineering Technologies and Management Research, 2024)
This research intended to examine how organizational culture mediates the relationship between leadership and social capital in Iraqi service enterprises. The research used a descriptive-analytical approach, collecting data from a sample of 341 managers working in service firms in Iraq using a questionnaire. Total of (341) suitable surveys were collected for statistical analysis; the study used SPSS and Amos software’s to analyses the collected data and tests the hypotheses. The results of the study indicated that there is no impact of Authoritative and Facilitative leadership on the social capital of service companies in Iraq, there is an impact of Democratic and Situational leadership on the social capital of service companies in Iraq, and there is an impact of organizational culture on the relationship between leadership and social capital of service companies in Iraq. In light of these findings, the study recommended the need to pay attention to the quality of leaders who are appointed in service companies in Iraq due to the clear impact of the quality of leadership at the level of social capital practices of companies.